PENINGKATAN PENDAPATAN DAERAH BERBASIS PADA USAHA MIKRO, KECIL, DAN MENENGAH - Nainggolan, Khairina; Cikusin, Yaqub; Hayat, Hayat (ARISTO, 2017)
The development of small and micro enterprises have a very important role in the development of the regional economy. it can be seen from the amount of employment opportunities provided by UMKM for the community. UMKM existence cannot be under timed, because UMKM have a proven able to with stand the economic crisis that occurred in Indonesia. However, Â in the development of UMKM cannot be separated from in habiting fact that hit existence of UMKM. Several classic problems that occur in UMKM is lack of capital in the developing the business, unhealthy market competition that still happening until now is the market competition with product made in china. Lack of information about the market network and still lack of innovation in creating new product-products. UMKM therefore very much require the role of government in the developing small andmiddlebusiness.